Wayang Palembang Dalam Lakon Bambang Dharmojati oleh Dalang Kiagus Wirawan Bersama Sanggar Sri Palembang - Aminatul Fadilla (Dance and Theatre Review, 2019)
This study aimed to analyzing the dynamics of the existence of the Wayang Palembang from the beginning of birth until that brought by Kiagus Wirawan with Sanggar Sri Palembang nowaday (2019). So, to be more focused, Bambang Dharmojati’s sample was chosen in order to give an overview of the Wayang Palembang performance. This research was conducted using qualitative methods and ethnographic approaches. During the process of research found that Wayang Palembang is a typical art that originated from Wayang Purwa. This art began to live and be known in the community since the collapse of the Palembang Darussalam sultanate. There were three very strong cultural elements in the Wayang Palembang, namely the Melayu Palembang, Java and Cirebon. Wayang Palembang today was experiencing a decline in audience interested. This phenomenon raises fundamental questions about how the Wayang Palembang performance, how Sanggar Sri Palembang survives and why it has decreased audience interested. For this reason, Hausers, Tomars and Wolff’s theories were used which said that social change in a place will present a unique art renewal in accordance with the social patterns of the community at that time, then Kernodle’s structured and textured theory was used to analyzing the form of performances to be able to presenting interpretations of interested preferences show. Furthermore, the way to survive is analyzed by Scott’s theory which said that efforts to fight and survive consist of open and hidden form resistance. The results of this study indicated that the Wayang Palembang performance today was still very classical in nature, resulting in a difference between public demand and the availability of performance space. However, to maintain its existence, Kiagus Wirawan and Sanggar Sri Palembang will always hold Wayang Palembang performances independently and do not care about the number of spectators.Keywords: Wayang Palembang; performance, society, Sanggar Sri Palembang; Bambang Dharmojati